Cross-border territories development as an indicator of the integration processes effectiveness - I. V. Mishchenko; E. G. Shustova; I. V. Milkina (Управление)
The development of cross-border territories and the impact of integration processes on them has been considered in the article. The creation of the Eurasian Economic Union becomes an impetus for the development of both the member states of the organization and their individual territories. This integration formation is relatively young, but today it creates a common market for the movement of goods, services, labor and capital. That is the cross-border territories, as bridges between countries, which feel the effect of the processes taking place in the common economic space: the trade turnover between the countries increases, as well as the inflow of investment and labor.The study is aimed at identifying the effect of integration processes on the development of two cross – border areas-Altai territory (Russian Federation) and East Kazakhstan region (Republic of Kazakhstan). The analysis showed, that the mutual trade turnover has increased between the countries and these territories; there is a good foundation for the development of cooperation in production. However, other indicators of socio-economic development have a negative trend. The outflow of population from these territories continues. The territories do not attract a significant amount of investment.The measures to increase the attractiveness of the Altai territory and East Kazakhstan region within the Eurasian Economic Union have been offered: strengthening production ties through the creation of industrial clusters; the inclusion of territories in the implementation of the project “economic belt of the silk road”; the use of the natural potential of the territories for the creation and development of joint tourist destinations. The measures proposed in the article will strengthen cooperation between cross-border territories, create favorable conditions for increasing the integration effect in these territories, developing infrastructure and cooperating in the main sectors of the border countries, strengthening financial ties and attracting investment.